URDU-ROLE AND IMPORTANCE OF FAMILY IN THE PREVENTION OF SEXUAL BEHAVIOR - Amber Ghani; Ismail Arfi (دی اسکالر, 2018)
Since his creation, man is more inclined towards peace than violence. To sustain this, he has taken possible steps in every category, either at government level, family level or individual. Islam has particularly focused the role of family in the betterment of society. Family is considered basic institution of the society, which comprises of parents, children and blood relations (mostly).  Society is form by the combinations of these families which shows the association between society and family. It wouldn’t be wrong to say, if family as an institution fulfill its responsibilities, society could be more peaceful and worth living place.Sexual abuses in society are tragic situation for families to live with, for that purpose initial prevention step should be taken for long term results. Families should be keener in parenting their children, as per the global trend, giving information of sexual behaviour is not that beneficial to cure the disease of harassment and rape Bonding between parents and children, belief of Allah should be imbedded in soul of children, confidence on themselves, modesty as per the Islamic teaching should be emphasised, self-defence training and self-awareness should be part of the subject, these are the basic steps to be followed for the security and benefit of individual, family as well as society. In the above stated issue and suggestions, purpose for this research is to find the main cause of sexual abuse and rectify it from its root by fully utilizing the role of family.